Lathrolestes buccinator Holmgren 1857 - Reshchikov, Alexey (Zenodo, 2012)
Lathrolestes buccinator (Holmgren, 1857) Material: specimens, female, 2males, Russia , Kamchatka, Kozyrevsk, deciduous., motley grass, 24.vii.1985, D. Kasparyan; female, Russia , Buryatia, 01.vii.1971, D. Kasparyan; 2females, Russia , Khabarovsky Kray, Khekhtsyr, Levaya river, coniferous-deciduous forest, 02.vii.1983, D. Kasparyan; male, Russia , Sakhalin, Aniva, 04.vii.1973, D. Kasparyan; male, Russia , Khabarovsky Kray, Vysokogorny, birch wood with Larix , 10.vii.1983, D. Kasparyan; female, Russia , Primorsky Kray, Anisimovka, 26–27.vi.1996, S. Belokobylskij. Distribution: Palearctic. Published as part of Reshchikov, Alexey, 2012, Review and key to Russian Far East Lathrolestes (Hymenoptera, Ichneumonidae), pp. 1-32 in Zootaxa 3414 on page 25, DOI: 10.5281/zenodo.281927